2020
DOI: 10.31219/osf.io/tbpx2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of the neurobiological effects of theta-burst stimulation (TBS) as measured using functional magnetic resonance imaging (fMRI)

Abstract: Theta burst stimulation (TBS) is associated with a range of clinical, cognitive, and behavioural outcomes, but specific neurobiological effects remain somewhat unclear. This systematic literature review investigated resting-state and task-based functional magnetic resonance imaging (fMRI) outcomes post TBS in healthy human adults. Forty-two studies that applied either continuous- or intermittent- (c/i) TBS, and adopted a pretest-posttest and/or sham-controlled design, were included. For resting-state outcomes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…While the neural changes associated with rTMS are out of the scope of this report, we need to explore the probability that repeated iTBS with a pause of 10 minutes may exert inhibitory effects in some participants. [51][52][53][54][55] Changes in the severity of catatonia or negative symptoms were noted between treatment arms. BFCRS total scores and BFCRS subscores indicating decreased motor activity were ameliorated with 1-Hz rTMS, whereas BNSS anhedonia scores improved with iTBS stimulation (eFigure 1 in Supplement 2).…”
Section: Discussionmentioning
confidence: 99%
“…While the neural changes associated with rTMS are out of the scope of this report, we need to explore the probability that repeated iTBS with a pause of 10 minutes may exert inhibitory effects in some participants. [51][52][53][54][55] Changes in the severity of catatonia or negative symptoms were noted between treatment arms. BFCRS total scores and BFCRS subscores indicating decreased motor activity were ameliorated with 1-Hz rTMS, whereas BNSS anhedonia scores improved with iTBS stimulation (eFigure 1 in Supplement 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our exciting findings have demonstrated that TMS restored the disrupted connectivity of DLPFC. A systematic review [62] has revealed that TBS possesses the capability to reverse functional connectivity, thereby exerting an impact on the functioning of diverse brain regions. These findings align with the hypothesized long-term depression (LTD) and long-term potentiation (LTP)-like plasticity effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous TBS studies stimulating the primary motor cortex have found that iTBS usually enhances cortical excitability, while cTBS suppresses cortical excitability, presumably reflecting long-term potentiation and long-term depression effects, respectively ( 61 , 62 ). TBS studies targeting the left parietal lobe observed increased functional connectivity in cognitive networks following iTBS and decreased functional connectivity in response to cTBS ( 63 ). Our study is in agreement with these previous findings and suggests that iTBS might cause memory enhancement compared to cTBS.…”
Section: Discussionmentioning
confidence: 99%